2017
DOI: 10.1038/s41598-017-17884-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Newly Committed Pancreatic Cells in the Adult Mouse Pancreas

Abstract: Multipotent epithelial cells with high Aldehyde dehydrogenase activity have been previously reported to exist in the adult pancreas. However, whether they represent true progenitor cells remains controversial. In this study, we isolated and characterized cells with ALDH activity in the adult mouse or human pancreas during physiological conditions or injury. We found that cells with ALDH activity are abundant in the mouse pancreas during early postnatal growth, pregnancy, and in mouse models of pancreatitis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
10
1
Order By: Relevance
“…The enzymatic activity of ALDH allows isolation by FACS using a fluorogenic ALDH substrate known as Aldefluor. In a previous report, we showed that ALDHexpressing cells have the ability to differentiate into b-cells after parturition (36). We further demonstrated that the Alde 1 cells in the adult pancreas can be divided into four distinct subpopulations on the basis of E-cadherin and CD90 expression (36).…”
Section: Appearance Of Lgr5-expressing Cells In the Pancreas During And After Pregnancymentioning
confidence: 52%
See 2 more Smart Citations
“…The enzymatic activity of ALDH allows isolation by FACS using a fluorogenic ALDH substrate known as Aldefluor. In a previous report, we showed that ALDHexpressing cells have the ability to differentiate into b-cells after parturition (36). We further demonstrated that the Alde 1 cells in the adult pancreas can be divided into four distinct subpopulations on the basis of E-cadherin and CD90 expression (36).…”
Section: Appearance Of Lgr5-expressing Cells In the Pancreas During And After Pregnancymentioning
confidence: 52%
“…In a previous report, we showed that ALDHexpressing cells have the ability to differentiate into b-cells after parturition (36). We further demonstrated that the Alde 1 cells in the adult pancreas can be divided into four distinct subpopulations on the basis of E-cadherin and CD90 expression (36). Under normal conditions, the Alde population consists mainly of CD90 À cells; however, the percentage of mice having CD90 1 cells increases concomitantly with gestation during pregnancy and peaks toward the end of gestation when Alde 1 / CD90 1 cells can be found in 75-80% of dams (36).…”
Section: Appearance Of Lgr5-expressing Cells In the Pancreas During And After Pregnancymentioning
confidence: 87%
See 1 more Smart Citation
“…Here (Fig.6C), we show those IDs that appeared on t-SNE plots within a specific stage or cell subpopulation. While few of the IDs were expected based on literature search, we propose that Carboxypeptidase E (CPE,(71), MAN1A (Mannosidase Alpha Class 1A Member 1,(72), and ALDH1A1 (aldehyde dehydrogenase 1 family member A1, (73) deserve a further consideration for the modulation of differentiation protocol efficiency and developmental research. All other protein IDs from Fig.3C were not clearly identified or were at minimal detection levels at both t-SNE plots.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, highly proliferative α-cell-like progenitors have also been described in the human pancreas throughout life, 48 as well as newly-committed endocrine progenitors in the mouse pancreas that selectively express high ALDH activity. 49 Either of these populations could be progenitors to Ins + Glut2 LO cells, or distinct progenitor pools that are amenable to HSC-induced expansion and differentiation to become functional β-cells. In summary, we showed that a single intrapancreatic injection of either MSC or HSC from mouse bone marrow can transiently improve glycemic control in diabetic mouse recipients, but with different time courses and likely different mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%